2012
DOI: 10.1063/1.4721896
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced magneto-thermoelectric power factor of a 70 nm Ni-nanowire

Abstract: Thermoelectric (TE) properties of a single nanowire (NW) are investigated in a microlab which allows the determination of the Seebeck coefficient S and the conductivity σ. A significiant influence of the magnetization of a 70 nm ferromagnetic Ni-NW on its power factor S²σ is observed. We detected a strong magneto thermopower effect (MTP) of about 10% and an anisotropic magneto resistance (AMR) as a function of an external magnetic field B in the order of 1%. At T = 295 K and B = 0 T we determined the absolute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 22 publications
2
26
1
Order By: Relevance
“…The resulting magneto-Seebeck phenomenon has also been observed in the magnetic-field dependence of inorganic thermoelectrics. [36][37][38] Notably, a magneto-Seebeck effect of 22% was reported in a 70 nm Ni-nanowire with a magnetic field strength B of 0.5 T. 37 The major difference between the previous reports and our current work on magneto-Seebeck effect is that the observation was limited to metallic samples. Our work demonstrates that the same effect can be observed in organic material which recently has been recognized as semi-metallic polymer.…”
contrasting
confidence: 52%
See 1 more Smart Citation
“…The resulting magneto-Seebeck phenomenon has also been observed in the magnetic-field dependence of inorganic thermoelectrics. [36][37][38] Notably, a magneto-Seebeck effect of 22% was reported in a 70 nm Ni-nanowire with a magnetic field strength B of 0.5 T. 37 The major difference between the previous reports and our current work on magneto-Seebeck effect is that the observation was limited to metallic samples. Our work demonstrates that the same effect can be observed in organic material which recently has been recognized as semi-metallic polymer.…”
contrasting
confidence: 52%
“…Our work demonstrates that the same effect can be observed in organic material which recently has been recognized as semi-metallic polymer. 39 Therefore, a relationship between magnetoresistance and thermopower S can be described using Mott's formula: S = (π 2 /3e)k 2 B T[∂lnG/∂E], for a conductance change G with band energy E. 37 It needs to be emphasized that this relation is established under the assumption that PEDOT:PSS presents metallic conductivity as previously reported, instead of being a Fermi glass. 39 In this respect, by using a magnetic field, we can change the thermopower by changing the conductance through magneto-resistance effect.…”
mentioning
confidence: 99%
“…They found that the Wiedemann-Franz law holds in the field-range of GMR even in the presence of weak inelastic scattering. However, despite of this comprehensive data on thermal conductivity and thermoelectricity of GMR materials, neither the magnetic field dependence of the thermoelectric figure of merit -the magneto-ZT -nor the field dependence of the power factor -the magneto-PF - [21] have been addressed so far.…”
mentioning
confidence: 99%
“…This leads to the conclusion, that the energy derivative of the resistivity in Mott's equation is independent of the magnetic field. By changing the spin configuration of a multilayer, the thermopower should also be changed, as inferred by different theoretical models [11,13,21]. However, concerning the Lorenz number L, there are two controversial conclusions.…”
mentioning
confidence: 99%
“…Several experiments have been illustrated it and open a new field, the so-called "Spin Caloritronics". Such experiments are for example the Spin-Seebeck Effect (SSE) [2], Spin Peltier effect [3] TEP in multilayer nanowires [4,5] or thermally induced spin torque in nonlocal lateral spin-valves [6]. Recently an equivalent to TMR for thermoelectric transport was observed, the tunnelling magnetothermoelectric power (TMTEP) [7].…”
Section: Introductionmentioning
confidence: 99%